Choice of radiotherapy modality for the combined treatment of non-small cell lung cancer with brain metastases: whole-brain radiation therapy with simultaneous integrated boost or stereotactic radiosurgery - Dong, Xiaotao; Wang, Kunlun; Yang, Hui; Li, Yan; Hou, Yanqi; Chang, Jiali; Yuan, Ling (Frontiers in Oncology, 2023)
Purpose To compare Whole-brain radiation therapy with simultaneous integrated boost (WBRT+SIB) to stereotactic radiosurgery (SRS)for non-small cell lung cancer (NSCLC)with brain metastases (BMs)in terms of overall survival (OS), intracranial progression-free-survival(iPFS), toxicity and objective response rate (ORR) Methods A retrospective review was performed in our hospital of 90 patients diagnosed with NSCLC- BM who received either SRS (n = 48) or WBRT+SIB (n = 42) from January 2016 to January 2022. 76 (84.44%) patients received systemic drug therapy after radiotherapy, including chemotherapy(n=53), targeted therapy(n=40), immunotherapy(n=23), and anti-vascular drug therapy(n=45). OS and iPFS were estimated by the Kaplan-Meier method and compared using the log-rank test. Univariate and Multivariate analysis of the prognostic factors was performed using the Cox proportional hazard regression model. Results The WBRT+SIB cohort had a longer median iPFS (20.0 versus (VS) 12.0 months, P = 0.0069) and a similar median OS (32.0 vs 28.0 months, P = 0.195) than the SRS cohort. Intracranial objective response rates in WBRT +SIB and SRS cohorts were 76.19% and 70.09%, respectively (P = 0.566). Disease control rates were 88.09% and 83.33%, respectively (P = 0.521). Multivariate analysis showed that WBRT+SIB is the only factor affecting iPFS(hazard ratio (HR):0.597 95%confidence interval(CI):0.370-0.966, P=0.035). Sex, Liver metastasis and Lymph node metastasis are risk factors for NSCLC-BM. Conclusion In the context of systemic drug therapy, WBRT+SIB may have better intracranial local control than SRS in NSCLC-BM patients.